Comparative Study Comparative Study in the Development of Agrarian Reform of the Indonesian Land Bank Agency with the Federal Law Development Authority (Felda) Malaysia - UTAMA, I Wayan Kartika Jaya; ABDULLAH, Mohd Kamarulnizam Bin; MAHENDRAWATI, Ni Luh Made; WESNA, Putu Ayu Sriasih; PERMATASARI, Indah; SUKANDIA, I Nyoman; AGUNG, Anak Agung Istri (Protection: Journal Of Land And Environmental Law, 2025)
The Land Bank Agency faces various challenges, these challenges include limited accurate spatial data, frequent agrarian conflicts between indigenous peoples, farmers, and large companies, and weak coordination between government institutions. In addition, policy implementation is often hampered by bureaucratic issues, overlapping regulations, and low community participation in the decision-making process. Therefore, an innovative approach and learning from best practices in other countries that have previously implemented similar policies are needed. One country that has long experience in implementing agrarian reform is Malaysia. Through the establishment of The Federal Land Development Authority (FELDA) in 1956. The type of research that researchers use in this study is a qualitative descriptive research method. The approach used in this study is normative juridical descriptive. The research was conducted by literature study to obtain legal materials and using document study techniques. The Malaysian land bank, FELDA, has been established for a long time, namely in 1956, compared to the Indonesian Land Bank Agency, which only had definite regulations in 2021 and FELDA has a different implementation mechanism compared to Indonesia, namely FELDA focuses more on implementing land banks in the agricultural sector, while the implementation of land banks in Indonesia tends to be relatively new.